Teaching and Learning: Motivating Learners - Isabella Damiani; Andrew C. Thoron; James C. Bunch (EDIS)
Motivation is a process that drives individuals forward. Educators must be aware of the continuum of motivation and appropriately provide opportunities for student engagement, learning, and growth. This 2-page document discusses how to motivate learners. Written by Isabella Damiani, Andrew Thoron, and J. C. Bunch and published by the UF/IFAS Department of Agricultural Education and Communication, May 2018. http://edis.ifas.ufl.edu/wc305